Taá¹bÄ«q Biá¹Äqah al-MufradÄt fÄ« Dars al-Lughah al-Ê¿Arabiyyah li Tarqiyah NatÄ'ij MahÄrah al-KalÄm - Lukman Syah, Burhan; Rahmanudin, Ii (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2023)
The purpose of this study is to describe the application of the vocabulary card to improve the results of teaching speaking skills for outstanding eighth-grade A students at the Islamic Junior High School 1 Getis Ponorogo and to describe the learning results after using an educational method, which is the vocabulary card. This research is of the classroom action research type. The researcher used the method of testing, observation, and written documents. As a result, the application of the vocabulary card improved the studentsâ€™ results in the Arabic language subject, and this was evident in the first round, as it obtained a result of 80% from 26 students. In the second round, 26 students obtained a result of 100%. After completing this research, the researcher recommended that students should be interested in learning speaking skills and that the teacher should apply the vocabulary card in teaching the Arabic language subject.Ø§Ù„Ù‡Ø¯Ù Ù…Ù† Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ÙˆØµÙ ØªØ·Ø¨ÙŠÙ‚ Ø¨Ø·Ø§Ù‚Ø© Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø¹Ù„Ù‰ ØªØ±Ù‚ÙŠØ© Ù†ØªØ§Ø¦Ø¬ ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø«Ø§Ù…Ù† A Ø§Ù„Ù…ØªÙÙˆÙ‚ ÙÙ‰ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø¬ÙŠØªÙŠØ³ ÙÙˆÙ†ÙˆØ±ÙˆÙƒÙˆ ÙˆÙˆØµÙ Ù†ØªØ§Ø¦Ø¬ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø¨Ø¹Ø¯ Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³ÙŠÙ„Ø© ØªØ¹Ù„ÙŠÙ…ÙŠØ© ÙˆÙ‡ÙŠ Ø¨Ø·Ø§Ù‚Ø© Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª. Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù…Ù† Ø§Ù„Ù†ÙˆØ¹ Ø§Ù„ÙØµÙ„ÙŠ Ø§Ù„Ø¥Ø¬Ø±Ø§Ø¦ÙŠ (Classroom Action Research)ØŒ Ø§Ø³ØªØ®Ø¯Ù… Ø§Ù„Ø¨Ø§ØØ« Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø±ØŒ ÙˆØ§Ù„Ù…Ù„Ø§ØØ¸Ø©ØŒ ÙˆØ§Ù„ÙˆØ«Ø§Ø¦Ù‚ Ø§Ù„Ù…ÙƒØªÙˆØ¨Ø©. ÙˆÙ…Ù† Ù†ØªÙŠØ¬Ø© Ø£Ù† ØªØ·Ø¨ÙŠÙ‚ Ø¨Ø·Ø§Ù‚Ø© Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª ØªÙ…ÙƒÙ†Øª Ù…Ù† Ø§Ù„Ø§Ø±ØªÙ‚Ø§Ø¡ Ø¨Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ù…Ø§Ø¯Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ°Ù„Ùƒ ØªØ¨ÙŠÙ† ÙÙŠ Ø§Ù„Ø¯ÙˆØ± Ø§Ù„Ø£ÙˆÙ„ Ø¨ØÙŠØ« ØØµÙ„ Ø¹Ù„Ù‰ Ù†ØªÙŠØ¬Ø© 80% Ù…Ù† 26 Ø·Ø§Ù„Ø¨Ø§. ÙÙŠ Ø§Ù„Ø¯ÙˆØ± Ø§Ù„Ø«Ø§Ù†ÙŠ ØØµÙ„ÙˆØ§ Ø¹Ù„Ù‰ Ù†ØªÙŠØ¬Ø© 100% Ù…Ù† 26 Ø·Ø§Ù„Ø¨Ø§. Ø¨Ø¹Ø¯ Ø§Ù„Ø§Ù†ØªÙ‡Ø§Ø¡ Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‚Ø¯Ù… Ø§Ù„Ø¨Ø§ØØ« ØªÙˆØµÙŠØ© Ù…ÙØ§Ø¯Ù‡Ø§ Ø£Ù† ÙŠÙ‡ØªÙ… Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¨ØªØ¹Ù„Ù… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù…ØŒ ÙƒÙ…Ø§ Ø£Ù† ÙŠØ·Ø¨Ù‚ Ø§Ù„Ù…Ø¯Ø±Ø³ Ø¨Ø·Ø§Ù‚Ø© Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ù…Ø§Ø¯Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©.Â